Estimation of contamination of ERS-2 and POSEIDON satellite radar altimetry close to the coasts of Australia - Deng, Xiaoli; Featherstone, Will; Hwang, C.; Berry, P. (Taylor and Francis, 2002)
It is broadly acknowledged that the precision of satellite-altimeter-measured instantaneoussea surface heights (SSH) is lower in coastal regions than in open oceans, duepartly to contamination of the radar return from the coastal sea-surface state and fromland topography. This study investigates the behavior of ERS-2 and POSEIDON altimeterwaveformdata in coastal regions and estimates a boundary around Australia's coastsin which the altimeter range may be poorly estimated by on-satellite tracking software. Over one million 20 Hz ERS-2 (March to April 1999) and POSEIDON (January 1998 toJanuary 1999) radar altimeter waveform data were used over an area extending 350 kmoffshore Australia. The DS759.2 (50 resolution) ocean depth model and the GSHHS(0.2 km resolution) shoreline model were used together to define the coastal regions. Using the 50% threshold retracking points as the estimates of expected tracking gate,we determined that the sea surface height is contaminated out to maximum distanceof between about 8 km and 22 km from the Australian shoreline for ERS-2, dependingpartly on coastal topography. Using the standard deviation of the mean waveforms as an indication of the general variability of the altimeter returns in the Australian coastalregion shows obvious coastal contamination out to about 4 km for both altimeters, andless obvious contamination out to about 8 km for POSEIDON and 10 km for ERS-2. Therefore, ERS-2 and POSEIDON satellite altimeter data should be treated with somecaution for distances less than about 22 km from the Australian coast and probablyignored altogether for distances less than 4 km.